Marble Maze Game Design Using Augmented Reality Technology - Mahtarami, Affan; Ertino, Eddo (Universitas Amikom Purwokerto, 2024)
Augmented Reality (AR) combines computer-generated graphic objects with real objects, so that virtual collaboration occurs between the two types of objects. The main purpose of AR is the use of computers as devices to facilitate a job done by humans. Based on its characteristics, AR has great potential to be used as a computer game platform. The research reported in this paper raises the issue of utilizing AR as a computer game platform. The research was conducted in the form of developing a marble maze computer game using AR with an emphasis on the interaction aspect. The lighting conditions of the playing environment have a crucial influence. To get a consistent appearance, adequate lighting is needed. However, AR-based games are one of the interesting games to play. The game must be played in well-lit environments, with a flash light, or with a high-sensitivity camera in order to get around this. Nonetheless, the majority of volunteers acknowledged that they were open to playing games that used augmented reality.